Myanmar Migration Assessment - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
Myanmar Migrant Assessment (MMA), is a comprehensive survey aimed at understanding the impacts and processes of migration in Myanmar amidst political instability, armed conflict, economic disruptions, and climatic shocks. Drawing its sample from the Myanmar Household Welfare Survey (MHWS), the MMA targeted households with members who had migrated within the past decade or relocated entirely since January 2021. Conducted via phone interviews between June and July 2023, the MMA surveyed 4,296 households, focusing on various aspects including migration, employment, and remittances. Migrants, as defined by the MMA, are household members who departed for over two months due to employment, marriage, safety concerns, or educational pursuits. Out of the surveyed households, 5,455 migrants were identified, with 3,505 still away from home and 1,487 having returned.